Urolithin A analog inhibits castration-resistant prostate cancer by targeting the androgen receptor and its variant, androgen receptor-variant 7 - Chandrasekaran, Balaji; Tyagi, Ashish; Saran, Uttara; Kolluru, Venkatesh; Baby, Becca V.; Chirasani, Venkat R.; Dokholyan, Nikolay V.; Lin, Jyh M.; Singh, Amandeep; Sharma, Arun K.; Ankem, Murali K.; Damodaran, Chendil (Frontiers in Pharmacology, 2023)
We investigated the efficacy of a small molecule ASR-600, an analog of Urolithin A (Uro A), on blocking androgen receptor (AR) and its splice variant AR-variant 7 (AR-V7) signaling in castration resistant prostate cancer (CRPC). ASR-600 effectively suppressed the growth of AR+ CRPC cells by inhibiting AR and AR-V7 expressions; no effect was seen in AR- CRPC and normal prostate epithelial cells. Biomolecular interaction assays revealed ASR-600 binds to the N-terminal domain of AR, which was further confirmed by Western blot and subcellular localization studies. Molecular studies suggested ASR-600 promotes ubiquitination of AR and AR-V7 resulting in the inhibition of AR signaling. Microsomal and plasma stability studies suggest that ASR-600 is stable, and its oral administration inhibited the tumor growth in CRPC xenografted castrated and non-castrated mice. In conclusion, our data suggests that ASR-600 enhances AR ubiquitination in both AR+ and AR-V7 CaP cells and inhibits their growth in in vitro and in vivo models